Moderating effect of strategic factor on organizational performance - Akpoviroro, Kowo Solomon; Owotutu, Sabitu Olalekan; Akanmu, Popoola Mufutau (Management and Entrepreneurship: Trends of Development, 2024)
Strategic factor plays an important role in determining firm’s performance even though it’s not clear whether firm size affect organizational performance. Therefore; an investigation is required to assess the effect firm size, location and structure will have on firm’s performance. For the purpose of this study primary data was used. The ex-post facto method was employed. The population consists of the members of staff of Guinness International PLC Plant, Lagos Nigeria. Yamane formula was adopted to determine the sample size. The data was analyzed using manual and electronic based methods through the data preparation grid and statistical package for the social sciences, (SPSS). Linear regression analysis method which also makes use of ANOVA was employed to test the hypothesis. The findings of this study have shown a positive relationship between Firm Size and competitive advantage such that competitive advantage is affected by Firm Size. A finding from the study also shows that there is significant relationship between organizational structure and firm performance. It was concluded that Strategic factors cannot be overemphasized in determine the size, structure and performance of firm. This study has made us understand the effect of strategic factor on firm performance and also revealed immense benefit to both local and international firms as well as useful to students for further research. More so, there was a positive relationship between Location and Profitability such that Location does not affect Profitability in the organization. This study will make organizations to understand the effect of strategic factor on firm performance and it will also be of immense benefit to both local and international firms as well as useful to students for further research. It will help management and manager to identify the effect of strategic factors on firm performance. For academician, the study will give more insight into the relationship between strategic factors and firm performance. JEL Classification: L10, L12, L21